Influence of Bilingualism on Language Development: A Systematic Review - Aayeshah Firdous; Naveed Babur; Saba Aziz; Fariha Ambreen; Sadaf Iftikhar; Ghulam Farid (Pakistan Journal of Medical & Health Sciences, 2024)
Background: This study examines the impact of bilingualism (English and Urdu) on language development, proficiency, and use, focusing on linguistic, cognitive, and social aspects, providing a comprehensive understanding. Methodology: This systematic review followed PRISMA guidelines and used reputable databases Scopus, PubMed and Google Scholar to gather data. The study included peer-reviewed articles published between 2016 and 2023, focusing on language development and structure in bilinguals speaking Urdu and English. The subjects were all ages, and studies excluded if they included secondary illnesses or developmental disorders. The final articles were selected through expert discussions. Findings: The study explores the impact of bilingualism on language development, focusing on morphological, syntactical, morphosyntactical, reading, and verbal pronunciation. It finds that bilingualism can improve comprehension, word learning, predictive skills, and metacognitive reading strategies. However, it can also lead to difficulties in phoneme learning and cross- linguistic interference. The study emphasizes the importance of equal exposure to both languages and educational plans that encourage vocabulary growth. It suggests that bilingual students should develop special reading techniques to enhance vocabulary acquisition. Practical implication: The study suggests that bilingual education programs should promote balanced literacy practices in Urdu and English, address linguistic issues, and support bilingualism and multiculturalism in schools. Teachers should be trained to address lower order English comprehension difficulties, and caregivers should encourage bilingual children at home and participate in cultural activities. Policies should encourage bilingual education and use multiple languages in schools, ensuring bilingual Urdu-English speakers are productive academically, interpersonally, and culturally. Conclusion: The systematic review highlights the positive impact of bilingualism on cognitive development, language proficiency, and social skills, despite initial challenges like smaller vocabulary sizes. It emphasizes the importance of adequate support for bilingual children. Keywords: Bilingualism, Language, Urdu & English, Cognitive, Language Development